Analysis of the Economic Value of Providing Binahong Leaves (Anredera Cordifolia) as a Substitute for Antibiotic Growth Promoter in Broiler Raising - Muhammad Naufal Tambunan; Yunilas; Muheri Indra Aja (Jurnal Peternakan Integratif, 2025)
Broiler rearing requires optimal productivity which will have implications for higher income.  However, broiler rearing requires innovation in maintaining their health.This study aims to determine the utilization of binahong leaves as a substitute for AGP which has an impact on the economic value of a broiler livestock rearing process. Study design used a completely randomized design (CRD) with 5 treatments and 4 replications, namely P0: no antibiotics and no infection, P1 = No antibiotics + 0.4 ml infection, P2 = commercial antibiotics + 0.4 ml infection, P3 = 7.5 gr binahong leaves / kg feed + 0.4 ml infection, and P4 = 15 gr binahong leaves / kg feed + 0.4 ml infection. The parameters observed were feed cost, feed price per body weight, economic value of feed, and income over feed cost. The results of the study were the provision of binahong leaf flour did not give a significant difference in the parameters of feed cost, and the economic value of feed. However, in the parameters of feed price per body weight and income over feed cost, the provision of binahong leaf flour had a significant effect.  In conclusion utilization binahong leaves has an impact on the economic value of a broiler livestock rearing process